The Effect of Passing Ball Games to Gross Motor Ability of Children with Special Need - Eko Qobul Muchlis Saputro; Dwi Gansar Santi Wijayanti (Journal of Physical Education Health and Sport, 2025)
Gross motor skill is crucial in child’s growth and development proses. Throwing ball games are considered effective in helping improve gross motor skills in children with special needs. The purpose of this study is to provide a comprehensive understanding of the influence of ball throwing games on gross motor skills in children with special needs. This study used a literature review method. The database used was from Google Scholar. The first stage of identification obtained 2500 articles. The second stage of screening, filtering 16 articles. The third stage of eligibility was 10 articles. After the eligibility stage, eight articles remained. The results of the discussion found that the activity of throwing a ball in a game of bocce can improve gross motor skills, stimulate nerves, and improve hand-foot coordination in children with mental retardation. Children with mild intellectual disabilities showed an increase in manipulative motor skills after being treated with a modified throwing ball game. From the results of the systematic review, it can be concluded that ball throwing games have a significant influence on gross motor skills in children with special needs.